(3GdEKHGJ HGdhSGFd GdYdejI GdMOjKI hSdWI GdbGVj GdLfGFj aj JbOjQgG (B/s - (3HgfS, jGSQ MSjfs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3GdEKHGJ HGdhSGFd GdYdejI GdMOjKI hSdWI GdbGVj GdLfGFj aj JbOjQgG jcJSH GdEKHGJ CgejI cHjQI aj GdOYhi GdLfGFjI hGdeOfjI Ydi MO ShGA, EP Hg jXgQ GdMb hjOMQ GdHGWd, hJUGf GdMbhb hjYe GdCef hGdGWeFfGf QHhY GdeLJeY, EP Ef GdEKHGJ jDcO GdMb Ch jfajg, EdG Cf gPg GdCgejI JROGO cKjQG aj eLGd GdEKHGJ GdLfGFj fXQG deG JeKdg GdLQjeI ef NQb dCef GdeLJeY hJbhjV dGSJbQGQg, hYdi VhA Pdc LGA cJGH (B((3GdEKHGJ HGdhSGFd GdYdejI GdMOjKI hSdWI GdbGVj GdLfGFj aj JbOjQgG(B) (3aj KdGKI aUhd eJfGhdG ehVhYGJ(B: ((3JYQja GdEKHGJ GdLfGFj hCgejJg hCfXeJg GdeNJdaI, hSGFd GdEKHGJ GdMOjKI, hSdWI GdbGVj GdLfGFj aj JbOjQ COdI GdEKHGJ(B)s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3JYQja GdEKHGJ GdLfGFj hCgejJg hCfXeJg GdeNJdaI (B: (3GdeHMK GdChd (B: (3GdJYQja HGdEKHGJ GdLfGFj(B... (3hehVhYGJ CNQi(B-(3GdaUd GdKGfj (B: (3hSGFd GdEKHGJ GdMOjKI (B: (3GdeHMK GdChd (B: (3GdhSGFd GdYdejI GdeTQhYjI aj GdEKHGJ GdLfGFj(B... (3hehVhYGJ CNQi(B-(3GdaUd GdKGdK (B: (3SdWI GdbGVj GdLfGFj aj JbOjQ COdI GdEKHGJ (B: (3GdeHMK GdChd (B: (3eG gjI GdSdWI GdJbOjQjI ddbGVj GdLfGFj heHHQGJgG hVhGHWgG(B... (3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B141-155.s
Keywords: (3GdEKHGJ GdLfGFjs; (3GdJMbjb GdLfGFjs; (3GdSdWI GdbVGFjIs; (3SdWI GdbGVjs; (3GdbQGFf GdbVGFjIs; (3GdGYJQGas